The Effects of Unstable Macroeconomic Indicators on Stock Price Behavior of Banking Sector in the Nigerian Stock Market - Ibrahim Bello Abdullahi (Binus Business Review, 2020)
The research aimed to investigate the stock price behavior of banking sector in response to unstable macroeconomic variables in the Nigerian stock market. The research employed ex-post facto research design, and the data were subjected to Autoregressive Distributed Lag method of analysis to examine both the short and long run of the studied variables between 2009 and 2018. The findings reveal significant negative effects of interest rate and foreign reserves on the stock price behavior of the banking sector in the long run. Meanwhile, the inflation rate has a significant positive influence on stock price behavior. Then, the exchange rate is not statistically significant in influencing stock price behavior in the Nigerian stock market. It can be concluded that the stock price behavior of banking sector is influenced by foreign external reserve, interest rate, and inflation rate. It is recommended that the monetary policy rate should be reduced to decrease the cost of borrowing and enhance liquidity level in the stock market.